Dissociative recombination and vibrational excitation of molecular cations with electrons: application to H2+, BeH+ and their isotopomers. Issue 17 (January 2020) - Pop, N; Iacob, F; Mezei, J Zs; Niyonzima, S; Motapon, O; Schneider, I F
Synopsis: Cross sections and Maxwell rate coefficients for the low-energy reactive collisions of electrons with Hydrogen and Beryllium hydride cations will be presented, as well as a discussion on the major relevant mechanisms and features – direct/indirect process, ro-vibronic couplings, ro-vibrational dependence.